2021
DOI: 10.3341/kjo.2020.0138
|View full text |Cite
|
Sign up to set email alerts
|

Association with Corneal Remodeling Related Genes, ALDH3A1, LOX, and SPARC Genes Variations in Korean Keratoconus Patients

Abstract: Purpose To determine whether the cornea remodeling-related genes aldehyde dehydrogenase 3A1 ( ALDH3A1 ), lysyl oxidase ( LOX ), and secreted protein acidic and rich in cysteine ( SPARC ) were potential susceptibility candidate genes for keratoconus in Korean patients, we investigated the associations of single nucleotide polymorphisms (SNPs) in these three genes in Korean patients with keratoconus. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, two preliminary results from the Polish [ 20 ] and Korean populations [ 21 ] suggested an association of ALDH3A1 variants with KC risk. The preliminary data from the Korean population were confirmed recently and the rs2228100 variant of ALDH3A1 was found to be strongly associated with KC risk [ 22 ].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, two preliminary results from the Polish [ 20 ] and Korean populations [ 21 ] suggested an association of ALDH3A1 variants with KC risk. The preliminary data from the Korean population were confirmed recently and the rs2228100 variant of ALDH3A1 was found to be strongly associated with KC risk [ 22 ].…”
Section: Introductionmentioning
confidence: 83%
“…This study is an extension of our results presented at the Association for Research in Vision and Ophthalmology (ARVO) annual meeting 2016 [ 20 ] for reporting the first time an association has been found of ALDH3A1 variants with KC in Poles. In addition, a recent study of the Korean population reported such an association (rs2228100 strongly associated with KC risk) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 21 , 52 , 53 The rs2956540 and rs10519694 are 2 well-known SNPs found in the fourth intron of the LOX gene and connected to KC in different populations. 8 , 12 , 29 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…Although OMIM links the gene to autosomal recessive osteogenesis imperfecta, missense variants in SPARC have been detected in patients with keratoconus, so the involvement of the gene in the pathology is possible. In addition, the proximal location of SPARC to the LOX gene, residing on chromosomes 5q31.3-q32 and 5q23.2, respectively, could also suggest its contribution to keratoconus [58]. A third variant in heterozygosis appears in the TTN gene (p.(Val24529Leu)), whose relationship with KC is argued in the OFT-00814 family [40].…”
mentioning
confidence: 99%